Molecular techniques in crop improvement (Kluwer Academic Publishers, 2002)
This book provides comprehensive information on the latest tools and techniques of molecular genetics and their applications in crop improvement. Advanced techniques used in molecular markers, QTL mapping, marker-assisted breeding and molecular cytogenetics have been thoroughly discussed